Large-volume flux closure during plasmoid-mediated reconnection in coaxial helicity injection. (23rd March 2016) - Ebrahimi, F.; Raman, R.
Abstract: A large-volume flux closure during transient coaxial helicity injection (CHI) in NSTX-U is demonstrated through resistive magnetohydrodynamics (MHD) simulations. Several major improvements, including the improved positioning of the divertor poloidal field coils, are projected to improve the CHI start-up phase in NSTX-U. Simulations in the NSTX-U configuration with constant in time coil currents show that with strong flux shaping the injected open field lines (injector flux) rapidly reconnect and form large volume of closed flux surfaces. This is achieved by driving parallel current in the injector flux coil and oppositely directed currents in the flux shaping coils to form a narrow injector flux footprint and push the injector flux into the vessel. As the helicity and plasma are injected into the device, the oppositely directed field lines in the injector region are forced to reconnect through a local Sweet–Parker type reconnection, or to spontaneously reconnect when the elongated current sheet becomes MHD unstable to form plasmoids. In these simulations for the first time, it is found that the closed flux is over 70% of the initial injector flux used to initiate the discharge. These results could work well for the application of transient CHI in devices that employ super conducting coils to generate and sustain the plasma equilibrium.